Local-to-global signal transduction at the core of a Mn2+ sensing riboswitch - Suddala, Krishna C; Price, Ian R; Dandpat, Shiba S; Janeček, Michal; Kührová, Petra; Šponer, Jiří; Banáš, Pavel; Ke, Ailong; Walter, Nils G (Nature communications, 2019)
The widespread Mn2+-sensing yybP-ykoY riboswitch controls the expression of bacterial Mn2+ homeostasis genes. Here, we first determine the crystal structure of the ligand-bound yybP-ykoY riboswitch aptamer from Xanthomonas oryzae at 2.96 Å resolution, revealing two conformations with docked four-way junction (4WJ) and incompletely coordinated metal ions. In >100 µs of MD simulations, we observe that loss of divalents from the core triggers local structural perturbations in the adjacent docking interface, laying the foundation for signal transduction to the regulatory switch helix. Using single-molecule FRET, we unveil a previously unobserved extended 4WJ conformation that samples transient docked states in the presence of Mg2+. Only upon adding sub-millimolar Mn2+, however, can the 4WJ dock stably, a feature lost upon mutation of an adenosine contacting Mn2+ in the core. These observations illuminate how subtly differing ligand preferences of competing metal ions become amplified by the coupling of local with global RNA dynamics.
Keywords: molekulární konformace; Ligands; signální transdukce; Models, Molecular; Molecular Conformation; Signal Transduction; mangan; ligandy; hořčík; Riboswitch; Xanthomonas; mutace; krystalografie rentgenová; bakteriální RNA; Escherichia coli; vazebná místa; Crystallography, X-Ray; Lactococcus lactis; molekulární modely; Binding Sites; regulace genové exprese u bakterií; simulace molekulární dynamiky; riboswitch; Manganese; Molecular Dynamics Simulation; konformace nukleové kyseliny; Gene Expression Regulation, Bacterial; Nucleic Acid Conformation; Mutation; RNA, Bacterial; Magnesium